IMPLEMENTASI SELF-VIDEO RECORDING TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS MAHASISWA NON BAHASA INGGRIS - Sarniati Nuru; Nurjannah; Nuzul Hijrah Safitri; Verawaty Nur Agista (Jurnal Bastra (Bahasa dan Sastra), 2025)
Majority of students at Halu Oleo University particularly in Non-English students are struggle in English course. The objective of this research is to investigate the implementation of self-video recording toward speaking skill of Non-English students. The participants of this research are students majoring in capture fisheries who enrolled in general English courses. The method that used in this research is qualitative research where the sampling was chosen purposively. Besides using speaking test, in this research also provides the interview, and spreading questionnaire to find out the students’ response or perception toward the use of self-video recording in teaching general English. Using speaking rubric assessment proposed by Brown (2004) which consist of 5 categories, such as: grammar, vocabulary, fluency, competence and pronunciation, the researcher analyses the students speaking achievement. The result shows that after implementing self-video recording there is an improvement in the form of speaking skill’s ability of Non-English students especially in vocabulary. Besides that, from the questionnaire, it reveals that self-video recording proposed positive response to be applied in speaking class of Non-English students. Keywords: English competency, Non-English Students, Communicative Language Teaching, Self-Video Recording